Pelatihan Akses Wisata Berbasis Digital pada Kelompok Usaha Penyeberangan Pulau Bokori - Sutiyana Fachruddin; Shinta Arjunita Saputri; Dian Trianita Lestari; Rizal Adi Saputra; Sultrayansa (Indonesian Journal of Community Services, 2022)
This Community Service Program aims to support the accessibility of technology-based tourist attractions in the era of globalization. This is based on the conventional method used by the object of service in serving tourists who will go to Bokori Island. Conventional means relying solely on information from person to person about their business. This is certainly ineffective, especially entering Society 5.0. era, where the focus is not only on the technological component but also on the human. Therefore, the service team offers a solution in the form of making a digital-based ship rental application (website) and assistance in its use in the form of training. This website is useful not only to advertise community businesses but also Bokori island tourism. The website will be managed by an admin who is a representative of the Bajoe village community. The features contained in this application are Bokori Island Tourism info, crossing points, checking ship availability, boat rental, and ticket printing. The presence of this application is certainly very useful for tourists, especially those from outside Kendari, they can order tickets in advance of the time they want to visit Bokori island. The community service program was positively welcomed by the local community, especially the crossing business owners because they felt helped by the application made by the service team.